Effects of chemoradiotherapy and chemotherapy on survival of patients with locally advanced pancreatic cancer: A meta-analysis of randomized controlled trials. Issue 36 (September 2018) - Wang, Cuiying; Liu, Xiaohua; Wang, Xiaohua; Wang, Yanlei; Cha, Na
Abstract : Abstract: To comparatively evaluate chemoradiotherapy (CRT) and chemotherapy (CT) for the treatment of locally advanced pancreatic cancer (LAPC) by meta-analysis. A literature search was performed until August 2016 to identify comparative studies assessing survival rates and complications. Pooled odds ratios (ORs) and 95% confidence intervals (95% CIs) were determined with the fixed or random effects model. Five randomized controlled trials (RCTs) met the defined inclusion criteria. A total of 593 patients were included, with 295 and 298 treated with CRT and CT, respectively. Overall survival showed no statistically significant difference in patients treated with CRT and CT at 6, 12, 18, and 24 months (respectively: OR = 1.13, 95% CI: 0.60–2.17; OR = 1.15, 95% CI: 0.53–2.52; OR = 1.13, 95% CI: 0.43–2.95; OR = 1.07, 95% CI: 0.67–1.72). Meanwhile, CRT had higher rates of grade 3 to 4 adverse events (nausea and vomiting, OR = 2.74, 95% CI: 1.36–5.52; diarrhea, OR = 4.28, 95% CI: 1.16–15.71). The data are not sufficient to change from CT to CRT in the treatment of patients with LAPC and thus clinical discretion is required until more data is accumulated.